PENGARUH LAYANAN PERPUSTAKAAN UMUM BERBASIS INKLUSI SOSIAL TERHADAP LITERASI INFORMASI MASYARAKAT DI DINAS KEARSIAPAN DAN PERPUSTAKAAN PROVINSI SUMATERA BARAT - Putra Ramadhan, Hafid; Elva Rahmah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of social inclusion-based public library services on public information literacy at the Archives and Library Service of West Sumatra Province. This study is motivated by the important role of libraries as centers of information and lifelong learning amidst the rapid development of information technology, which demands that the public have good information literacy skills. This study uses a quantitative approach with a descriptive method. The study population was 75 people, with a sample of 74 respondents determined using the Slovin formula with a 5% error rate. The data collection technique was carried out through a questionnaire using a Likert scale. The research variables consist of social inclusion-based public library services as the independent variable (X) which includes service accessibility, equality and non-discrimination, community participation, service relevance to social needs, and community empowerment and capacity building. Meanwhile, the dependent variable (Y) is public information literacy which includes the ability to identify information needs, search for information, evaluate information, utilize information, and use information ethically and legally. The results of the study indicate that social inclusion-based public library services are in the good category and have a significant influence on public information literacy. This indicates that the better the quality of services provided, the higher the level of public information literacy. This finding confirms that libraries play a role not only as information providers but also as agents of community empowerment through inclusive and participatory services. Therefore, strengthening library services based on social inclusion needs to be continuously developed to sustainably improve the quality of public information literacy.